Additional Data on the History of István Csekey’s Transfer to the Public Law Department in Pécs - Schweitzer, Gábor (Díké - Journal of Dezső Márkus Research Group for Comparative Legal History, 2020)
István Csekey (1889–1963), professor of Hungarian public law, taught at the University of Pécs Faculty of Legal and Political Sciences from 1946 to 1951. The former professor of the University of Szeged was invited to Pécs after his predecessor, Kálmán Molnár was invited to the University of Budapest. A preparatory committee was set up to fill the vacancy at the Department of Public Law in Pécs. Professor Kálmán Molnár prepared a report for the committee. The unpublished report, which remained in Kálmán Molnár’s file, is an important source, not only because it provides a complete overview of the current situation of the discipline of public law including the scientific works of István Csekey, but also highlights the professional criteria on which a department position was intended to be filled.